Ethnobotanical study of medicinal plants by indigenous community of Aek Guo Village, Mandailing Natal District, Indonesia - RIDAHATI RAMBEY; FEBRISA NELASUFA; ASEP PERRY MUHAMMAD ATHORIEZ; SOLIHIN SOLIHIN; RAHMAWATY RAHMAWATY; ARIDA SUSILOWATI; YUNUS AFIFUDDIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Rambey R, Nelasufa F, Athoriez APM, Solihin, Rahmawaty, Susilowati A, Afifuddin Y. 2024. Ethnobotanical study of medicinal plants by indigenous community of Aek Guo Village, Mandailing Natal District, Indonesia. Biodiversitas 25: 1046-1056. Aek Guo Village, Mandailing Natal District, Indonesia, falling under the jurisdiction of Forest Management Unit or Kesatuan Pengelolaan Hutan (KPH) IX Panyabungan, serves as a home for the Mandailing indigenous tribe, primarily engaged in agriculture with a significant dependence on the forest for sustenance. Within the cultural fabric of the Aek Guo community, there exists a profound tradition of employing medicinal plants as an alternative form of treatment, a practice deeply rooted in ethnobotanical knowledge passed down through generations. The study aimed to identify the diverse array of medicinal plants, their utilization practices, and key parameters such as Use Value (UV), Family Use Value (FUV), Plant Part Value (PPV), and Fidelity Level (FL) associated with their applications. A comprehensive approach that integrates qualitative and quantitative methods, the study involves semi-structured interviews and meticulous documentation. The findings reveal a rich repertoire of 66 plant species distributed across 36 families, constituting a vital component of the Aek Guo community. Noteworthy is the pre-eminence of ginger (Zingiber officinale) with the highest UV value (0.68), while paku gajah (Angiopteris evecta) being the lowest (0.01). Family Use Value (FUV) demonstrated variations, with Fabaceae leading the chart (0.39), and Simaroubaceae recording the lowest value (0.01). A closer examination of Plant Part Value (PPV) indicated a preference for leaves, comprising 56.06% of the utilized plant parts, while flowers contribute minimally at 1.51%. Fidelity Level (FL) values, crucial for assessing the significance of particular plants within the community, peak for kumis kucing (Orthosiphon aristatus) and ginger (Z. officinale) at 22.54%. In contrast, jerangau (Acorus calamus), pasak bumi (Eurycoma longifolia), salam (Syzygium polyanthum), and paku gajah (A. evecta) exhibit the lowest FL values at 1.41%. These findings contribute significantly to the broader understanding of ethnobotanical practices across different Mandailing communities, with potential implications for conservation, healthcare, and sustainable resource management.